Green construction project management and cost oversight - Kubba, Sam (Elsevier/Architectural Press, 2010)
Written in a conversational manner, this book will clarify the nuts and bolts of green construction, finance, and cost monitoring, and will outline the many attributes required to be successful in this field. The author draws on over 30 years of personal experience across the world - both as an employee and as an employer. The reader will learn how to plan and implement sound business strategies and form alliances in a global context. The book also offers important information and penetrating insights into the process of setting up and working as a due-diligence consultant.